Modern studies in property law. Volume 9 - Conway, Heather; Hickey, Robin ([Oxford] : Hart Publishing, 2017)
"This book contains a collection of peer-reviewed papers presented at the Eleventh Biennial Modern Studies in Property Law Conference held at Queen's University Belfast in April 2016. It is the ninth volume to be published under the name of the Conference. The Conference and its published proceedings have become an established forum for property lawyers from around the world to showcase current research in the discipline. This collection reflects the diversity and contemporary relevance of modern research in property law. Following a foreword from the keynote speaker at the Conference, Queen's alumnus Lord Kerr of Tonaghmore, the chapters address a range of issues, from the nature of land law and property rights, through claims to the home and digital assets, to the growing debate on the nature of public property. Collectively the chapters demonstrate the vibrancy and importance of property law in dealing with modern concerns across the common law world."--Bloomsbury Publishing.
pt. A. Land law and the nature of property rights in land -- pt. B. Life and death in property law -- pt. C. Fraud and title -- pt. D. Property, place, and development.
Includes bibliographical references and index.
Also issued in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Electronic reproduction.
Keywords: Landlord and tenant -- England; Landlord and tenant -- Wales; Property -- England; Property -- Wales; Real property -- England; Real property -- Wales